Giunto nel luogo che volli fuggire. Il canto CX d’Ausiàs March. - Cataldi, Pietro; Pasqual, Cèlia Nadal (Scripta, 2022)
The essay reflects on the ways in which March’s CX poem processes inner experience under the pressure of the madness of love. In particular, it reflects on the coexistence of synchronic and diachronic ways of living and representing the movements of the subject, in the light of a prismatic configuration of consciousness. Related to this, the essay identifies in the composition the topos of conversion, but transported to a secular level, and therefor incapable of a real internal transformation. On the basis of that, the essay notes the constitutive differences with respect to the models of Dante and Petrarch, which are also present.